1994
DOI: 10.1161/01.atv.14.10.1631
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic manifestations of common carotid atherosclerosis in elderly eastern Finnish men. Prevalence and associations with cardiovascular diseases and risk factors.

Abstract: We investigated the prevalence and associations with cardiovascular symptoms, signs, and risk factors of common carotid atherosclerosis using B-mode ultrasonography in a population sample of 182 eastern Finnish men aged 70 to 89 years. Men were examined in 1989 as a part of the 30-year follow-up examination of the eastern Finnish cohort of the Seven Countries Study. The mean maximal intima-media thickness (IMT) of the right and left common carotid arteries was 1.5 mm (range, 0.7 to 5.3 mm; standard deviation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 32 publications
2
40
1
Order By: Relevance
“…The carotid artery IMT is known to have a positive correlation with various atherosclerotic risk factors, such as age, blood pressure, total cholesterol, and LDLcholesterol [16][17][18][19][20]. The correlation coefficients between IMT and age (r = 0.520 in healthy subjects; r = 0.429 in diabetic patients) were similar to previous studies [21][22][23].…”
Section: Discussionsupporting
confidence: 86%
“…The carotid artery IMT is known to have a positive correlation with various atherosclerotic risk factors, such as age, blood pressure, total cholesterol, and LDLcholesterol [16][17][18][19][20]. The correlation coefficients between IMT and age (r = 0.520 in healthy subjects; r = 0.429 in diabetic patients) were similar to previous studies [21][22][23].…”
Section: Discussionsupporting
confidence: 86%
“…A cross-sectional study of Finnish elderly men reported a lack of the association between carotid mineralizations and clinical cardiovascular disease. 15 We did not have a significant excess risk of total or ischemic stroke associated with calcified plaque. The CHS also reported a nonsignificant relative risk of 6.93 (95% CI, 0.8 to 60.2) for incident stroke with calcified plaque.…”
Section: Discussionmentioning
confidence: 64%
“…In the present study, the definition of plaque was in accordance with the Mannheim Carotid Intima–Media Thickness and Plaque Consensus from 2004,11 in which cIMT ≥1.5 mm was considered as a plaque, whereas earlier studies used other definitions. In addition, the studies have included either older4, 21 or younger patients,3, 5, 23 men only,21 or examination of only 1 artery 5…”
Section: Discussionmentioning
confidence: 99%